The Genetic Aspect of Non-Syndromic Cleft Lip and Palate towards Candidate Genes in the Etiology : A literature Review - Mala Kurniati; RM Coen Pramono D; Agung Sosiawan; Ni Wayan Tirtaningsih (Institute of Medico-legal Publications Pvt Ltd, 2021)
Cleft lip and cleft palate (CL/P) is a cleft lip deformity indicated by an opening or an uncommon cleft in the lip or roof of the mouth (palate). The differences in ethnicity, gender, and the correlation with genetic factors influence the prevalence of Non-syndromic CL/P. This study was conducted through a literature review on genes that were allegedly associated with Non-syndromic CL/P. Genetics play a role, to a greater or lesser extent, in all diseases. Besides, palatogenesis involves many diverse genes in a complex process. In this case, oral cleft phenotypes develop when this process is disrupted in some manner because of gene dysfunction. Various genetic approaches, including genome-wide and candidate gene association studies as well as linkage analysis, have been undertaken to identify etiologic factors, but results have often been inconclusive or contradictory. Therefore, it concludes that the genetic basis of CL/P is still controversial because of the genetic complexity of clefting.